Barangay leader's handbook - Esguerra, Renato S. (Quezon City Ram Publishing Co., 1997)
This handbook aims to provide a comprehensive guide for every barangay leader in the aspects of affairs administration. It is also a source of information on communication, planning, project, budgeting, management, basic information, leadership, good citizenship, and reference. This handbook provides a guide on becoming effective barangay leaders.
Keywords: Local government -- Philippines -- Handbooks, manuals, etc; Barangay officials and employees -- Handbooks, manuals, etc; Local officials and employees -- Philippines -- Handbooks, manuals, etc; Barangay officials and employees -- Handbooks, manuals, etc